Halal Certification Models in Increasing Community Purchase Intention for Halal Products in Indonesia - Ari Agung Nugroho; Esaka Pratala; Atik Atikah (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The purpose of this research is to investigate the analysis of the implementation of the halal certification policy on the public's halal awareness, which has an impact on increasing people's purchasing power for halal products. The research sample was taken from 100 consumers who use Halal products in Indonesia. In this study, data analysis used a partial least square approach using Smart PLS software. The results of the analysis revealed that the implementation of the halal certification policy was found to be positively related to consumer halal awareness. Likewise, this study found a significant relationship between halal certification and people's buying interest in halal products. Furthermore, the policy of applying for halal certification is positively associated with an increase in people's purchasing power for halal products. Keywords: halal certification, halal awareness, purchase intention